2007
DOI: 10.1002/jcp.21057
|View full text |Cite
|
Sign up to set email alerts
|

D‐glucose stimulation of L‐arginine transport and nitric oxide synthesis results from activation of mitogen‐activated protein kinases p42/44 and Smad2 requiring functional type II TGF‐β receptors in human umbilical vein endothelium

Abstract: Elevated extracellular D-glucose increases transforming growth factor beta1 (TGF-beta1) release from human umbilical vein endothelium (HUVEC). TGF-beta1, via TGF-beta receptors I (TbetaRI) and TbetaRII, activates Smad2 and mitogen-activated protein kinases p44 and p42 (p42/44(mapk)). We studied whether D-glucose-stimulation of L-arginine transport and nitric oxide synthesis involves TGF-beta1 in primary cultures of HUVEC. TGF-beta1 release was higher ( approximately 1.6-fold) in 25 mM (high) compared with 5 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
4
27
2
Order By: Relevance
“…The stability of LM synthesis in CMs after cytokine stimulation differs from previous reports that demonstrated an enhancement of LM synthesis after TGF-b treatment (Jiang et al, 2005;Kawano et al, 2000). This observation may be related to a low response of CMs to TGF-b and TNF-a, as only doses of 15 and 100 ng/ml of these cytokines, respectively, were able to induce FN expression, whereas lower doses (1-2 ng/ml) stimulate other cell types (Va´squez et al, 2007). Additionally, even if LM expression was stimulated by the cytokines, the competency of different cells to assemble basement membranes is regulated by expression of sulfated glycolipids, which is the first step in the anchoring of LM molecules to the cell surface triggering LM matrix assembly (Li et al, 2005).…”
Section: Discussioncontrasting
confidence: 80%
“…The stability of LM synthesis in CMs after cytokine stimulation differs from previous reports that demonstrated an enhancement of LM synthesis after TGF-b treatment (Jiang et al, 2005;Kawano et al, 2000). This observation may be related to a low response of CMs to TGF-b and TNF-a, as only doses of 15 and 100 ng/ml of these cytokines, respectively, were able to induce FN expression, whereas lower doses (1-2 ng/ml) stimulate other cell types (Va´squez et al, 2007). Additionally, even if LM expression was stimulated by the cytokines, the competency of different cells to assemble basement membranes is regulated by expression of sulfated glycolipids, which is the first step in the anchoring of LM molecules to the cell surface triggering LM matrix assembly (Li et al, 2005).…”
Section: Discussioncontrasting
confidence: 80%
“…PCR experiments demonstrated that HAECs expressed mRNA for hCAT1 and hCAT2B, but not hCAT2A, as has previously been reported in HUVECs [19]. One previous study in HUVECs has reported that incubation in high glucose for 6 h markedly increased hCAT1 mRNA levels [20], yet the level of hCAT1 protein was not reported. In the current study, hCAT1 and hCAT2 protein levels in HAECs were unaffected by glucose culture concentration, indicating that the glucose-stimulated change in arginine transport is likely to reflect a change in activity, rather than expression of the hCAT isoforms.…”
Section: Discussionsupporting
confidence: 65%
“…That plasma arginine decreases to a greater extent following glucose ingestion suggests that increased plasma glucose may be stimulating intracellular arginine uptake by upregulating CAT-1 expression. However, mRNA expression of CAT-1 increases at $4 h in endothelial cells treated with glucose (51,52) and no studies to our knowledge have examined this effect at earlier time points. Furthermore, increased oxidative stress following glucose ingestion may upregulate arginase in endothelial cells, resulting in greater intracellular arginine degradation and may contribute to hyperglycemia-mediated impairments in vascular function.…”
Section: Discussionmentioning
confidence: 95%